Laki – laki 30 Tahun dengan Skizofrenia Paranoid - Melati Indah Jelita; High Boy K. Hutasoit (CV. Jasa Sukses Abadi, 2021)
Emergency psychiatry is unforeseen circumstances with the potentiality ofkatastrophic, which 12% of emergency departments presented with psychiatric complaints. Violence or aggressiveness is the most common reason patients are admitted to emergency room, with attacking behavior seen in 3-10% in psychiatric patients. Many medical diseases commonly present with behavioral pathology and may lead to a change in thinking and mood. Schizophrenia is a functional psychosis with major abnormalities in thought processes and disharmony between thought processes, affect or emotion, will and psychomotor, accompanied by distortions of reality that lasts for at least 6 months and includes at least 1 month of active phase symptoms. Meanwhile, schizophrenic disorders are characterized by positive symptoms, negative symptoms, and cognitive impairment. There are several types of schizophrenia (paranoid, hebephrenic, catatonic, undifferentiated, and residual). Mr P, 30 years old came with complaints of attack his neighbors with a knife. In patient, there are perceptual disorders in the form of auditory hallucinations, and disturbances of thought content in the form of suspicious and chasing thoughts that have occurred since 4 years ago and tend to be alone. The patient was diagnosed with paranoid schizophrenia and was given therapy in the form of psychotherapy, psychoeducation, and psychopharmaceutical.